The acute effects of bilateral ovariectomy or adrenalectomy on progesterone, testosterone and estradiol serum levels depend on the surgical approach and the day of the estrous cycle when they are performed - Cruz María-Esther; Everardo Pamela M; Montiel Cristina; Mendoza Fernando D; Velasco Jacqueline; Gallegos Alma I; Flores Angélica; Domínguez Roberto (BMC, 2008)
Abstract Bilateral ovariectomy or adrenalectomy are experimental tools used to understand the mechanisms regulating the hypothalamus-pituitary-ovarian and the hypothalamus-pituitary-adrenal axis. There is evidence that acute unilateral perforation of the dorsal peritoneum in rats results in significant changes in progesterone, testosterone and estradiol serum concentrations. Because different surgical approaches for unilateral or bilateral ovariectomy or adrenalectomy, sectioning the superior ovarian nerve or the vagus nerve are used, we compare the acute effects on hormone serum concentrations resulting from the unilateral or bilateral dorsal approach to performing bilateral ovariectomy or adrenalectomy with those obtained when an unilateral incision is performed in the ventral abdomen. In general, the progesterone, testosterone and estradiol serum concentrations were higher in animals with ventral approach than in those with dorsal surgery, the effects varying depending on the day of the estrous cycle when surgery was performed. The results suggest that the neural signals arising from different zones of the peritoneum and/or the abdominal wall play different roles in the mechanisms regulating steroid hormones concentrations.